Potential Attenuating Effect of Single Bolus Dose of Esmolol on Cardiovascular Stress Response in Elective Neurosurgical Cases - Islam, Md Zahedul; Akter, Suraya; Kamal, Shahid (Community Based Medical Journal, 2022)
A prospective, double blind and randomized study was conducted in the Department of Anesthesiology of Dhaka Medical College Hospital, Dhaka, Bangladesh, between January 2013 and January 2014, to assess the efficacy of single bolus dose of esmolol (1.5mg/kg) to attenuate the cardiovascular stress response in elective neurosurgical cases. A total of 100 elective neurosurgical patients were enrolled in this study. Patients were randomly allocated equally into two groups: group A and group B, having 50 patients in each group. Patients of group A received intravenous esmolol (1.5mg/kg), 3 minutes before induction, while patients of group B received intravenous 10 ml of normal saline 3 minutes before induction. Parameters like heart rate, systolic and diastolic blood pressure were recorded before induction and every alternative minute for 10 minutes after endotracheal intubation. There were no differences in baseline demography of the patients (P>0.05). However, our data showed that in group A, there were significant reductions in heart rates immediately after induction, 1 minute, 3 minutes and 5 minutes after endotracheal intubation (P<0.01), as well as significant reductions in systolic and diastolic blood pressure after 1 minute, 3 minutes and 5 minutes of endotracheal intubation (P<0.01) respectively, in comparison to group B. Besides, reductions in rate pressure product were observed immediately after induction and 1 minute, 3 minutes and 5 minutes after endotracheal intubation respectively in group A, as compared to group B (P<0.01). In summary, a single bolus dose of esmolol (1.5mg/kg) effectively attenuates the cardiovascular stress response during and after laryngoscopy and endotracheal intubation in elective neurosurgical cases. CBMJ 2022 July: vol. 11 no. 02 P: 96-101